2000
DOI: 10.1093/jnen/59.12.1094
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Advanced Glycation End-Products for Cultured Cortical Neurons

Abstract: The Maillard reaction that leads to the formation of advanced glycation end-products (AGEs) plays an important role in the pathogenesis of angiopathy in diabetic patients and in aging. AGEs are believed also to contribute to the pathology of Alzheimer disease (AD) and other neurodegenerative processes. Incubation of cortical neurons with 5 immunochemically distinct AGEs, designated AGEs-1 to -5, produced a dose-dependent increase in neuronal cell-death, as assessed by MTT assay, Trypan blue and Hoechst 33258 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(162 citation statements)
references
References 40 publications
11
144
1
2
Order By: Relevance
“…However, they constitute a small percentage of circulating AGEs in vivo, and their biological relevance in endothelial dysfunction has remained unclear (35,36). In this study, we measured glyceraldehydederived AGEs to examine the role of AGEs and sRAGE in endothelial dysfunction because we previously found that 1) serum levels of glyceraldehyde-derived AGEs are elevated under inflammatory and/or diabetic conditions and correlated with vascular inflammation evaluated by 18F-fluorodeoxyglucose-positron emission tomography in humans; 2) this type of AGE mimics the biological effects of AGE-rich serum purified from diabetic patients on hemodialysis; and 3) deleterious and cytopathic effects of the AGE-rich serum were neutralized by addition of an antiglyceraldehyde-derived AGE-specific antibody but not by other types of anti-AGE antibodies (35)(36)(37)(38)(39). Therefore, although glyceraldehyde, which could be derived from glucose metabolism, is not a major sugar in vivo, and its incubation with proteins will generate a large number of structurally unidentified AGEs, and we cannot identify the structure of AGEs measured in this study, our study suggests the clinical utility of measurement of the ratio of serum levels of glyceraldehyde-derived AGEs to sRAGE for detecting endothelial dysfunction in humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, they constitute a small percentage of circulating AGEs in vivo, and their biological relevance in endothelial dysfunction has remained unclear (35,36). In this study, we measured glyceraldehydederived AGEs to examine the role of AGEs and sRAGE in endothelial dysfunction because we previously found that 1) serum levels of glyceraldehyde-derived AGEs are elevated under inflammatory and/or diabetic conditions and correlated with vascular inflammation evaluated by 18F-fluorodeoxyglucose-positron emission tomography in humans; 2) this type of AGE mimics the biological effects of AGE-rich serum purified from diabetic patients on hemodialysis; and 3) deleterious and cytopathic effects of the AGE-rich serum were neutralized by addition of an antiglyceraldehyde-derived AGE-specific antibody but not by other types of anti-AGE antibodies (35)(36)(37)(38)(39). Therefore, although glyceraldehyde, which could be derived from glucose metabolism, is not a major sugar in vivo, and its incubation with proteins will generate a large number of structurally unidentified AGEs, and we cannot identify the structure of AGEs measured in this study, our study suggests the clinical utility of measurement of the ratio of serum levels of glyceraldehyde-derived AGEs to sRAGE for detecting endothelial dysfunction in humans.…”
Section: Discussionmentioning
confidence: 99%
“…We found that (a) five distinct classes of AGE structures circulate in the blood of individuals with diabetic nephropathy on hemodialysis (DM-HD), (b) neurotoxic effects of serum fraction from DM-HD containing various AGEs structures are completely neutralized by the addition of antibodies raised against glyceraldehyde-derived AGEs, and (c) this type of AGE mimics the deleterious effects of AGE-rich serum purified from DM-HD on endothelial cells (85,102). Furthermore, because of the stronger binding affinity to RAGE (103), glyceraldehyde-derived AGEs are considered to be more toxic than glucose-derived AGEs.…”
Section: Measuring Serum Levels Of Ages and Its Clinical Utilitymentioning
confidence: 99%
“…Intracellular and extracellular accumulation of the AGEs detected in glaucomatous tissues may have different cytotoxic consequences facilitating the progression of neurodegeneration (Takeuchi et al, 2000a). For example, intracellular aggregates of AGEs detected in RGCs, their axons, and glia in glaucomatous eyes may interfere with normal cellular functions, including axonal transport and intracellular protein traffic (Cullum et al, 1991).…”
Section: Potential Consequences Of Ages In the Glaucomatous Optic Nermentioning
confidence: 99%